2022
DOI: 10.3390/diagnostics12010165
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Structure MRI in Diagnosing Autism

Abstract: This study proposes a Computer-Aided Diagnostic (CAD) system to diagnose subjects with autism spectrum disorder (ASD). The CAD system identifies morphological anomalies within the brain regions of ASD subjects. Cortical features are scored according to their contribution in diagnosing a subject to be ASD or typically developed (TD) based on a trained machine-learning (ML) model. This approach opens the hope for developing a new CAD system for early personalized diagnosis of ASD. We propose a framework to extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…Machine learning algorithms belongs to the second group of methods. ASD can be diagnosed using machine learning by analyzing genes ( Gunning and Pavlidis, 2021 ; Lin et al, 2021 ), brain ( Yahata et al, 2016 ; Eslami et al, 2019 ; Payabvash et al, 2019 ; Conti et al, 2020 ; Jiao et al, 2020 ; Doi et al, 2021 ; ElNakieb et al, 2021 ; Garbulowski et al, 2021 ; Gui et al, 2021 ; Leming et al, 2021 ; Liu et al, 2021 ; Nunes et al, 2021 ; Shi et al, 2021 ; Takahashi et al, 2021 ; Ali et al, 2022 ; Alves et al, 2023 ; ElNakieb et al, 2023 ; Martinez and Chen, 2023 ), retina ( Lai et al, 2020 ), eye activity ( Vabalas et al, 2020 ; Cilia et al, 2021 ; Liu et al, 2021 ; Kanhirakadavath and Chandran, 2022 ), facial activity ( Carpenter et al, 2021 ), human behavior ( Tariq et al, 2018 ; Drimalla et al, 2020 ) or movement ( Alcañiz Raya et al, 2020 ). Quiet a few researchers have reviewed the application of machine learning in autism detection.…”
Section: Related Workmentioning
confidence: 99%
“…Machine learning algorithms belongs to the second group of methods. ASD can be diagnosed using machine learning by analyzing genes ( Gunning and Pavlidis, 2021 ; Lin et al, 2021 ), brain ( Yahata et al, 2016 ; Eslami et al, 2019 ; Payabvash et al, 2019 ; Conti et al, 2020 ; Jiao et al, 2020 ; Doi et al, 2021 ; ElNakieb et al, 2021 ; Garbulowski et al, 2021 ; Gui et al, 2021 ; Leming et al, 2021 ; Liu et al, 2021 ; Nunes et al, 2021 ; Shi et al, 2021 ; Takahashi et al, 2021 ; Ali et al, 2022 ; Alves et al, 2023 ; ElNakieb et al, 2023 ; Martinez and Chen, 2023 ), retina ( Lai et al, 2020 ), eye activity ( Vabalas et al, 2020 ; Cilia et al, 2021 ; Liu et al, 2021 ; Kanhirakadavath and Chandran, 2022 ), facial activity ( Carpenter et al, 2021 ), human behavior ( Tariq et al, 2018 ; Drimalla et al, 2020 ) or movement ( Alcañiz Raya et al, 2020 ). Quiet a few researchers have reviewed the application of machine learning in autism detection.…”
Section: Related Workmentioning
confidence: 99%
“…sMRI is commonly used to examine brain morphology because of its high contrast sensitivity, spatial resolution, and the fact that it does not need exposure to ionizing radiation; this is especially significant for children and adolescents ( Ali et al, 2022 ). sMRI delivers various sequences of brain tissue (e.g., T1, T2, and FLAIR) created by altering excitation and repetition durations to view multiple brain regions ( Eslami et al, 2021 ).…”
Section: Structural Magnetic Reasoning Imaging and Features Extractionmentioning
confidence: 99%
“…Morphometric features include two main types, geometric and volumetric features, which can be employed for the MRI-based diagnosis of ASD. Geometric features are two-dimensional surface features associated with the cerebral cortex, such as curvature, surface area, and thickness ( Ali et al, 2022 ). While volumetric features usually refer to the size of the subcortical structures [e.g., white matter (WM) volume] ( Ecker et al, 2010 ).…”
Section: Structural Magnetic Reasoning Imaging and Features Extractionmentioning
confidence: 99%
“…It is increasingly possible to use MRI to assist in the diagnosis of ASD. One study (Ali et al, 2022) found that ASD could be successfully identified using anatomical features of the brain. Furthermore, another (Dekhil et al, 2020) introduced a computer‐aided diagnosis system (CAD) that enabled the prediction of ASD from TD individuals (accuracy >0.75) using sMRI and rs‐fMRI features of the brain across the ABIDE database.…”
Section: Introductionmentioning
confidence: 99%